Emerging applications of multirate signal processing and wavelets in digital communications - Wornell, G.W. (Proceedings of the IEEE, 1996)
Multirate systems and filter banks have traditionally played an important role in source coding and compression for contemporary communication applications, and many of the key design issues in such applications have been extensively explored. We review developments on the comparatively less explored role of multirate filter banks and wavelets in channel coding and modulation for some important classes of channels. Some representative examples of emerging potential applications are described. One involves the use of highly dispersive, broadband multirate systems for wireless multiuser communication (spread spectrum CDMA) in the presence of fading due to time-varying multipath. Another is the wavelet-based diversity strategy referred to as "fractal modulation" for use with unpredictable communication links and in broadcast applications with user-selectable quality of service. A final example involves multitone (multicarrier) modulation systems based on multirate filter banks and fast lapped transforms for use on channels subject to severe intersymbol and narrowband interference. Collectively, these constitute intriguing, interrelated paradigms within an increasingly broad and active area of research.